Technology Roadmaps for Compound Semiconductors - Bennett, Herbert S. ([Gaithersburg, MD] : U.S. Dept. of Commerce, National Institute of Standards and Technology, 2000)
The roles cited for compound semiconductors in public versions of existing technology roadmaps from the National Electronics Manufacturing Initiative, Inc., Optoelectronics Industry Development Association, Microelectronics Advanced Research Initiative on Optoelectronic Interconnects, and Optoelectronics Industry and Technology Development Association (OITDA) are discussed and compared within the context of trends in the Si CMOS industry. In particular, the extent to which these technology roadmaps treat compound semiconductors at the materials processing and device levels will be presented for specific applications. For example, OITDA’s Optical Communications Technology Roadmap directly connects the information demand of delivering 100 Mbit/s to the home to the requirement of producing 200 GHz heterojunction bipolar transistors with 30 nm bases and InP high electron mobility transistors with 100 nm gates. Some general actions for progress towards the proposed International Technology Roadmap for Compound Semiconductors (ITRCS) and methods for determining the value of an ITRCS will be suggested. But, in the final analysis, the value added by an ITRCS will depend on how industry leaders respond. The technical challenges and economic opportunities of delivering high quality digital video to consumers provide concrete examples of where the above actions and methods could be applied.